Pengembangan Sistem Informasi Pengarsipan File Menggunakan Metode R&D - Mauludy, Muh Wildan; Fathahillah (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
This research adopts the Research and Development method technique or better known as R&D, which is developing a product in the form of a system specifically designed to archive files in the form of documents at PT. THE AGE OF SELF-RELIANCE. The approach used is the ADDIE (Analyze, Design, Develop, Implement, and Evaluate) model. The subject of the study was an employee who used a system with samples taken from 2 employees through a simple random sampling technique, the limitations of the employees made the samples taken few. Data was collected using questionnaires and in-depth interviews, then analyzed based on ISO 25010 criteria which included eight characteristics: functionality, reliability, performance efficiency, portability, maintainability, usability, compatibility, and security. The test results show that the characteristics of functional suitability reach 100%, reliability 97%, performance efficiency 94%, portability 100%, usability 90%, maintainability 100%, security with alert level 0, and compatibility 100%. The conclusion of the study is that this system can be used effectively in the archiving of documents related to corporate archives and has met all the characteristics of ISO 25010. It is recommended that companies conduct periodic evaluations and updates of the system to ensure optimal performance and better data security.